2020
DOI: 10.1088/1361-6528/abc19f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of chosen noble metals as reactive oxygen species scavengers

Abstract: Reactive oxygen species (ROS) play an important role in various physiological processes of living organisms. However, their increased concentration is usually considered as a threat for our health. Plants, invertebrates, and vertebrates including humans have various enzymatic and non-enzymatic defence systems against ROS. Unfortunately, both bad condition of surrounding environment and unhealthy lifestyle can interfere with an activity of enzymes responsible for a regulation of ROS levels. Therefore, it is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Herein, a novel trimetallic AuPtCo nanopolyhedron with inherent peroxidase-and catalase-like catalytic activities has been synthesized via a one-step reduction method (Scheme 1A). In this nanocomposite, noble metal Au with excellent electron-transfer efficiency can be easily functionalized by coordination bonding, 27 while the transition metal Co 28 and noble metal Pt 29 with the intrinsic peroxidase-and catalase-like catalytic properties can enhance the CL intensity of the ABEI− H 2 O 2 system (Scheme 1B). Significantly, the surface biofunctionalization of AuPtCo (AuPtCo@Bio) endows the catalyst with a diffusion-controlled effect to generate a glowtype CL, which is further used to fabricate CL biosensors for sensitive detection of H 2 O 2 and lipoprotein-associated phospholipase A 2 (Lp-PLA 2 ) in real samples, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Herein, a novel trimetallic AuPtCo nanopolyhedron with inherent peroxidase-and catalase-like catalytic activities has been synthesized via a one-step reduction method (Scheme 1A). In this nanocomposite, noble metal Au with excellent electron-transfer efficiency can be easily functionalized by coordination bonding, 27 while the transition metal Co 28 and noble metal Pt 29 with the intrinsic peroxidase-and catalase-like catalytic properties can enhance the CL intensity of the ABEI− H 2 O 2 system (Scheme 1B). Significantly, the surface biofunctionalization of AuPtCo (AuPtCo@Bio) endows the catalyst with a diffusion-controlled effect to generate a glowtype CL, which is further used to fabricate CL biosensors for sensitive detection of H 2 O 2 and lipoprotein-associated phospholipase A 2 (Lp-PLA 2 ) in real samples, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast, animal cell membranes have less net charge and are rich in cholesterol to strengthen membrane integrity, and hence are less susceptible to the positively charged DAO/DEX 5.0 -CNGs. In addition, animal cells possess various cellular antioxidant enzymes, which can regulate the cellular ROS [ 36 39 ]. Similarly, the antioxidant-related enzymes in shrimp cells, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) can avoid damage caused by oxidative stress [ 40 43 ], implying that DAO/DEX5.0-CNGs is a safe feed additive for shrimp aquaculture.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies have reported that reactive oxygen species (ROS) produced in plants under various biotic and abiotic stresses cause oxidative stress (Ivanova et al, 2021). When ROS production and antioxidant defenses are out of balance, this leads to oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%